A study on the genus Glaucorhoe, with descriptions of two new species from China (Lepidoptera: Geometridae: Larentiinae) - Wu, Chunguang; Han, Hongxiang; Xue, Dayong (Zootaxa, 2008)
Chinese material of the Palearctic geometrid genus Glaucorhoe Herbulot is reassessed, with the description of two new species G. magaria sp. nov. and G. exilaria sp. nov. Illustrations of adults and genitalia of all the species are provided.